Influence of Ca substitution on microstructure and electrical properties of Ba(Zr,Ti)O3ceramics - Nuttapon Pisitpipathsin (2018)
In the present work, lead-free (Ba 1-x Ca x )(Zr 0.04 Ti 0.96 )O 3 (x=0.00-0.09) ceramics were fabricated via a solid-state reaction method. The microstructure and electrical properties of the ceramics were investigated. The microstructure of the BCZT ceramics showed a core shell structure at compositions of x=0.03 and 0.06. The substitution of small amount of Ba 2+ by Ca 2+ resulted in an improvement of the piezoelectric, dielectric and ferroelectric properties of the ceramics. The orthorhombic-tetragonal phase transition was found in the composition of x≤0.03. Piezoelectric coefficient of d 33 ∼392 pC/N and lowest E c ∼3.3 kV/cm with highest P r ∼14.1 μC/cm 2 were obtained for the composition of x=0.03 while its Curie temperature (T C ) was as high as 125 °C. However, the ferroelectric to paraelectric transition temperature had slightly shifted towards room temperature with increasing Ca 2+ concentration. © 2012 Elsevier Ltd and Techna Group S.r.l.